A Motion Control Scheme for a WMR Based on Input-Output Feedback Linearization and PID - Serralheiro, Werther (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2019)
This paper presents a trajectory tracking control scheme for an underactuated wheeled mobile robot (WMR). The WMR model used includes the robot kinematics and dynamics, as well as some DC motor nonlinearities. The proposed control scheme contains two loops: the inner one is a PID controller that handles the dynamics, and the outer one deals with the kinematics, using a input-output feedback linearization of the Follow the Carrot approach. Some different shapes of trajectories are devised in order to analyze the feasibility of the method.